Leber hereditary optic neuropathy (LHON) in a 6-year-old boy with a transient spinal cord lesion - Gök, Anıl; Cırdı, Gökçe; Deniz, Adnan; Sakarya Güneş, Ayfer; Tekin Orgun, Leman; Kara, Bülent (The Turkish Journal of Pediatrics, 2026)
Background. Leber hereditary optic neuropathy (LHON) is a maternally inherited mitochondrial disorder that predominantly manifests as bilateral, painless vision loss in young males. While traditionally associated with the optic nerves, a subset of patients exhibits additional neurological symptoms, referred to as LHON-plus syndrome. Involvement of the spinal cord is uncommon, particularly among the pediatric population, and may result in diagnostic challenges, potentially leading to confusion regarding acquired demyelinating diseases.Case Presentation. We report a 6-year-old boy with near-complete vision loss in the right eye and blurred vision in the left eye. Demyelinating diseases were suspected in the case of acute bilateral optic neuropathy. Cranial and orbital magnetic resonance imaging (MRI) showed no demyelinating lesions, whereas spinal MRI revealed a T2-hyperintense lesion at the C3–C6 levels. Due to unresponsiveness to conventional treatment for demyelinating diseases, genetic testing confirmed the homoplasmic m.11778G>A variant in NADH dehydrogenase subunit 4 (MT-ND4), establishing an LHON diagnosis. Spinal cord involvement supported the LHON-plus syndrome classification. Idebenone therapy was initiated, and follow-up was scheduled. During the 1.5-year follow-up, right eye visual loss persisted, while the left eye showed gradual vision decline. A second spinal MRI performed at 6 months showed complete resolution of the previous lesion without new lesions.Conclusion. Since optic neuropathy and spinal cord involvement typically indicate demyelinating diseases, these should be prioritized in initial evaluation due to their frequency and need for early immunomodulatory treatment. However, spinal cord involvement can occur in mitochondrial diseases, as demonstrated in this case. The presence of a transient and asymptomatic spinal cord lesion in this patient expands the recognized spectrum of central nervous system involvement in LHON. Therefore, LHON-plus syndrome should be considered when spinal cord involvement accompanies optic neuropathy after excluding other demyelinating diseases.
Keywords: Leber hereditary optic neuropathy; LHON-plus syndrome; optic neuropathy; mitochondrial disease; MT-ND4 m.11778G>A mutation